The Moderating Roles Of Environmental, Social and Governance Disclosures On Company Ownership Structure And Tax Avoidance - Rika Nur Widiastutik; Syaiful Iqbal; Moh. Khoiru Rusydi (Universitas Muhammadiyah Malang, 2024)
Purpose: The aim of this study is to investigate the moderating roles of environmental, social, and governance disclosures in the relationship between company ownership structure and tax avoidance was investigated. The company ownership structure consists of family ownership, foreign ownership, and institutional ownership. Methodology/approach: Quantitative is the type of this research with using secondary data. Data collected from company reports that is annual reports, sustainability reports, and OSIRIS database. The data was analyzed using hypothesis tests. Findings: The results of this study demonstrated that family ownership has a positive influence and foreign ownership has a negative influence, while institutional ownership has no influence on tax avoidance. Furthermore, this study revealed that environmental, social, and governance disclosures can weaken the influence of family ownership relationships, strengthen the influence of foreign ownership relationships, and prevent tax avoidance. In addition, environmental, social, and governance disclosures cannot moderate roles the influence of the relationship between institutional ownership and tax avoidance. Practical implications: The tax authority can improve the regulations about procedures for implementing transfer price agreements in special company relationships by considering environmental, social, and governance disclosures, so as to prevent an increase in tax avoidance. Originality/value: This study adds environmental, social, and governance disclosures to classify the inconsistency previous research which are thought to have a combined influence on the relationship between company ownership structure and tax avoidance.